(untitled) (Research, Society and Development, 2020)
Objetive: This study aimed to report an experience in simulation in Integrated Multidisciplinary Health Residency Program and its contribution to patient safety. Methods: Experience report on the use of simulation as a teaching and learning method for a multidisciplinary residents teamwork. Results: The activity was divided into three stages, a first stage was the brief, represented by the preparation of the scenario, the second, by the execution of simulation activity and the third, the moment of debriefing, with the total duration of activity of 48 minutes. Conclusion: Simulation contributed to learning by enabling a better integration between theoretical and practical knowledge, clinical reasoning development, effective communication, leadership and teamwork. Simulation allowed the development of technical and non-technical skills, allowing greater integration between professionals from different areas and instrumentalizing teamwork, contributed to improve the quality and safety of health care.